1686 Are We Addressing the Syndesmosis in All Ankle Fractures – 2nd Cycle Audit at an MTC. (12th October 2021) - Arora, N
Abstract: Aim: Assess compliance with BOAST guidelines – "Surgery should aim to achieve reduction and stabilisation of the ankle mortise. The syndesmosis should then be assessed and stabilised if unstable." Method: 103 Ankle ORIF procedures done for closed malleolar fractures in skeletally mature induviduals over a 12-month period used for first audit. Review of Op notes and intra-operative images was done looking for evidence of assessment of syndesmotic stability. Results were presented to the department and specific guidance on assessment of syndesmosis distributed. 84 Ankle ORIF procedures performed in next 12-month period used to re-audit. Results: In the first audit, 34% cases had inadequate documentation regarding the stability of syndesmosis. This is similar to finding of 32% in a previous audit in 2018. Re-audit after presentation and review of guidelines, showed improved compliance with only 14.3% cases having no documentation of syndesmosis status. Conclusions: Distribution of evidence supporting assessment of syndesmosis and making all grades of surgeons aware of the relevant guideline led to an improved compliance of more than 85%. There always remains the vulnerability to miss syndesmotic injuries and potentially adversely affect patient outcomes, if not explicitly assessed on table after bony fixation. All surgeons and rotating trainees need to be aware of this requirement.